Parables: applied economics literature about the impact of genetically engineered crop varieties in developing economies - Smale, Melinda; Zambrano, Patricia; Falck-Zepeda, José B.; Gruère, Guillaume P. (International Food Policy Research Institute, 2006)
A vast literature has accumulated since crop varieties with transgenic resistance to insects and herbicide tolerance were released to farmers in 1996 and 1997. A comparatively minor segment of this literature consists of studies conducted by agricultural economists to measure the farm-level impact of transgenic crop varieties, the size and distribution of the economic benefits from adopting them, consumer attitudes toward GE products, and implications for international trade. This paper focuses only on the applied economics literature about the impact of transgenic crop varieties in non-industrialized agricultural systems, with an emphasis on methods. A number of studies have surveyed the findings for both industrialized and non-industrialized agriculture, at various points in time, but surveys of methods are less frequent and have typically examined only one overall question or approach. Clearly, the methods used in research influence the findings that are presented and what they mean. Understanding the methods therefore enhances understanding of the findings. Four categories of impact analysis are considered: farmers, consumers, industry and trade. In part due to methodological limitations and the relatively brief time frame of most analyses, results are promising, but the balance sheet is mixed. Thus, findings of current case studies should not be generalized to other locations, crops, and traits. The aim of this review is to progress toward the defining a “best practices” methodology for national researchers who seek to produce relevant information about emerging crop biotechnologies for national policymakers.